LPA5 signaling is involved in multiple sclerosis-mediated neuropathic pain in the cuprizone mouse model - Ryoko Tsukahara; Shinji Yamamoto; Keisuke Yoshikawa; Mari Gotoh; Tamotsu Tsukahara; Hiroyuki Neyama; Satoshi Ishii; Noriyuki Akahoshi; Keisuke Yanagida; Hayakazu Sumida; Masatake Araki; Kimi Araki; et al. (Elsevier, 2018)
Lysophosphatidic acid (LPA) and LPA1 receptor signaling play a crucial role in the initiation of peripheral nerve injury-induced neuropathic pain through the alternation of pain-related genes/proteins expression and demyelination. However, LPA and its signaling in the brain are still poorly understood. In the present study, we revealed that the LPA5 receptor expression in corpus callosum elevated after the initiation of demyelination, and the hyperalgesia through Aδ-fibers following cuprizone-induced demyelination was mediated by LPA5 signaling. These data suggest that LPA5 signaling may play a key role in the mechanisms underlying neuropathic pain following demyelination in the brain. Keywords: LPA5, Neuropathic pain, Multiple sclerosis